Educational Attainment and Employment Outcomes: A Study on the Synergy Between Higher Education and Labor Market - Babameto, Etleva (Pedagogika Społeczna Nova, 2025)
The contemporary dynamics in a new interconnected and interrelated world and digital technology-driven society call for an increased skill-based and market-oriented education system. Within this setting, higher education as a nodal point between learning and work, is expected to equip students with relevant skills and competencies not only to find stable employment after graduation, but also to adapt them to labor market needs. This paper analyses the synergy between higher education and labor market both theoretically and empirically. European policies and initiatives on modernization of higher education in the context of global trends and digital society, efforts to reform Higher Education in the Western Balkans, characteristics of educational attainment and labor market are initially explored within the theoretical framework of the paper. Following a combination of qualitative and quantitative research method, the analysis aims to answer the research question of why there is a mismatch between higher education and labor market and how to fix it. In order to grasp the dynamics of higher education performance, interpret certain phenomena and identify and address the drivers of such a discrepancy, the analysis looks into a rich stock of primary sources – documents, laws, reports, and websites of official statistics agencies as well as secondary sources available to come up with recommendations for a quality and effective higher education system that leads to long-term graduates’ career accommodation at home and abroad.